Idioms as means of expressing consent in the dialogical discourse (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article is devoted to the issue of phraseological means expressing the consent relations in the dialogical discourse. The focus is made on stylistic and connotational features of idioms (with the meaning of mutual understanding) used in the works’ language of Ukrainian writers of XІX–ХХІ century.
Keywords: dialogue; consent; connotation; stylistic features; expressivity; emotionality; valuation; idiom